Bone Marrow and Pancreatic Islets: An Old Story with New Perspectives - Fabio Ciceri; Lorenzo Piemonti (Cell Transplantation, 2010)
In the past years, in the field of β-cell replacement for diabetes therapy, the easy availability of bone marrow (BM) and the widely consolidated clinical experience in the field of hematology have contributed to the development of strategy to achieve donor-specific transplantation tolerance. Recently, the potential role of BM in diabetes therapy has been reassessed from a different point of view. Diverse groups investigated the contribution of BM cells to β-cell replacement as direct differentiation into insulin-producing cells. More importantly, while direct differentiation is highly unlikely, a wide array of experimental evidences indicates that cells of BM origin are capable of facilitating the survival or the endogenous regeneration of β-cells through an as yet well-defined regeneration process. These new experimental in vitro and in vivo data will expand in the near future the clinical trials involving BM or BM-derived cells to cure both type 1 and type 2 diabetes in humans. In this review we recapitulate the history of use of BM in diabetes therapy and we provide clinically relevant actual information about the participation of BM and BM-derived stem cells in islet cell regeneration processes. Furthermore, new aspects such as employing BM as “feeder tissue” for pancreatic islets and new clinical use of BM in diabetes therapy are discussed.